Upaya Meningkatkan Ketrampilan Writing Skill pada Teks Interaksi Interpersonal dengan Menerapkan Teknik Pembelajaran Total Physical Response (Pada Siswa Kelas VII A SMP Negeri 8 Muaro Jambi) - Astuti Astuti (Universitas Batanghari Jambi, 2020)
The purpose of this study is to find out and improve writing skills in interpersonal interaction texts. his study uses two learning methods, namely the conventional method in the initial pre-cycle conditions and the Total Physical Response learning technique. The learning process is divided into three stages are the first stage is pre-cycle using conventional methods, the second stage of cycle 1 with the Total Physical Response method and the third stage of cycle 2 also uses the Total Physical Response method. The results showed that in the pre-cycle researchers were still using conventional methods in learning, only 11 students completed the study in the pre-cycle or 42% of students had finished learning. Then in cycle 1 the researcher conducted an improvement in learning by applying the Total Physical Response Learning Technique. The result is that in cycle 1 the number of students who have completed learning has increased to 20 students or 77% of students who have completed learning. In cycle 2 there was an increase in the number of students completing learning to 24 students or 92% of students being able to complete learning. So that it can be concluded in a period of approximately 2 weeks, with the concept of 4X meetings. The application of Total Physical Response Learning Techniques has a positive impact on the process of improving students' writing skills in Interpersonal Interaction Texts in Class VII A, SMP Negeri 8 Muaro Jambi.